Strategi Pemerintah Desa Dalam Proses Pengendalian Schistosomiasis Di Desa Watumaeta Kecamatan Lore Utara Kabupaten Poso - sefia dewi, jesica; Djaelangkara, Rizali; Mayusa, Askar (JPS: Journal of Publicness Studies, 2024)
The aim of this research is to find out the Village Government's Strategy in the Process of Controlling Schistosomiasis in Watumaeta Village, North Lore District, Poso Regency." The theory used is Koteen's theory in Salusu (1996: 104-105) which consists of 4 indicators including organizational strategy, program strategy, resource support strategy and institutional strategy. The basis of this research is qualitative with a descriptive research type. The data sources used are primary data and secondary data. There were 8 informants involved in this research with the determination of informants using purposive means. Data sources in this research include primary data and secondary data. Data collection techniques used include observation, interviews and documentation. With data analysis methods through data collection, data presentation, data reduction and drawing conclusions. The results of this research show that the Village Government's strategy in the process of controlling schistosomiasis in Watumaeta Village, North Lore District, Poso Regency has not been running optimally. This is based on the fact that the 4 Koteen theoretical indicators used as benchmarks are still not good in implementation.